Net energy, protein and macrominerals requirements for 70 to 120 day old female rabbits - Ferreira, R. G.; Carregal, R. D.; Resende, Kleber Tomás de [UNESP] (Associação Francaise Cuniculture, 1998)
In order to determine the net energy, protein and macrominerals requirements of 70 to 120 day old, 52 female White New Zealand rabbits, weighing 1900g +/- 40g were used. At the beginning of the experimental period, 14 of the 52 young does were slaughtered and the 38 remaining animals were kept under two dietary management: ad libitum and restricted feeding. Slaughters were performed to determine each nutrient body content. The weight gain nutrient requirements depicted by the quantities of each nutrient stored into the body were obtained by applying the regression equation, which estimate the empty body nutrient content logarithm as a function of the empty body weight logarithm, as described by ARC (1980). By determining the heat production logarithm at the zero level of metabolizable energy intake, the maintenance net energy requirement was estimated to be 45.31 Kcal/day/Kg(0.75) the mean net energy. protein, calcium, phosphorous, sodium, magnesium and potassium requirements for each gram of weight gain per day were estimated to be, 2.51 Kcal, 0.21g, 0.02g, 0.005g, 0.001g, 0.0004g and 0.002g, respectively.